Education, status and income - An established triangle disrupted by new qualifications? - Annen, Silvia [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2017)
"This article examines the relations between employees' educational attainment and their income as well as their social status, considering the individuals' social background. The data derive from the German BIBB/BAuA Employment Survey 2012. Social status is analyzed for the individuals' first job and their current job using the International Socio-Economic Index of Occupational Status (ISEI)." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; Erwerbstätiger; Bildungsabschluss; Einkommenshöhe; Korrelation; Regressionsanalyse; BIBB-/BAuA-Erhebung; Sozialer Status